PENGARUH MENDENGARKAN MUSIK TERHADAP MOOD BELAJAR PADA MAHASISWA MANAJEMEN DAKWAH UIN SUSKA RIAU - Lailatul Izzah Izzah (Nathiqiyyah, 2020)
The purpose of this study was to study the picture of student learning atmosphere and to study the influence of musk in the learning atmosphere of the third semester students of Da'wah Management UIN Suska T.A. 2019/2020 Pekanbaru. The method used in this study is a field survey research using questionnaires, interviews and observations, data analysis techniques used in this study with descriptive techniques. The sample in this study denied 36 third semester students of Da'wah Suska Riau Management in the academic year 2019/2020 who had a mood in learning in the lace category. Data collection techniques in this study used a learning mood questionnaire, interviews, observation and documentation as supporting techniques. The results of this study found that 75% of students listen to music while studying work on college assignments and 25% of students listen to music when there is no lecture. 80% of students who listen to music have the same reason they listen to learning compilation music, which is so they don't get bored while studying, because their hobbies are listening to music and increasing their creativity in thinking, adding vocabulary. While 13.3% of students who listen to music have reason to listen to music while learning to make them calm. And a reasonable break listening to music while learning makes learning that can be learned easily, can eliminate nervousness and likes the singer. 80% of students who listen to music when learning to listen to a type of music that is glance (pop and k-pop).